1988
DOI: 10.1152/physiologyonline.1988.3.5.189
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lymph: Vital for the Kidney and Valuable for the Physiologist

Abstract: Drainage of extravasated proteins from the interstitium is a vital function of renal lymph. In addition, it has a valuable role as a source of information about the renal interstitium. Information uniquely provided by lymph allows characterization of macromolecular permeabilities of postglomerular exchange vessels in the renal cortex under physiological conditions and in disease, e.g., in experimental diabetes mellitus. Various defense mechanisms are discussed that are instrumental in keeping the balance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As such, transplantable tumor lines, akin to those presented here, were not developed. One of the major advantages of SRC grafting over traditional subcutaneous grafting is the high tumor take rate (94%) and success rate of transplantable tumor line development (44%); largely due to the vascularization of the kidney (40,41). The abundant supply of nutrients, hormones, growth factors, and oxygen to transplanted cells and tissues (before they become vascularized) at the SRC site is likely instrumental to the success of the engraftment, and the conservation of patient tumor properties (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…As such, transplantable tumor lines, akin to those presented here, were not developed. One of the major advantages of SRC grafting over traditional subcutaneous grafting is the high tumor take rate (94%) and success rate of transplantable tumor line development (44%); largely due to the vascularization of the kidney (40,41). The abundant supply of nutrients, hormones, growth factors, and oxygen to transplanted cells and tissues (before they become vascularized) at the SRC site is likely instrumental to the success of the engraftment, and the conservation of patient tumor properties (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…39 Consequently, there is an exceptionally high fluid circulation within the extracellular space of the kidney. 40 This provides high graft perfusion, and the abundant supply of nutrients, hormones, growth factors and oxygen to transplanted cells and tissues (before they become vascularized) is likely instrumental to the success of the engraftment. 41 42 43 44 45 Access to the graft site is relatively easy via a small incision into the back of the host.…”
Section: Src Grafting Of Prostatic Tissuesmentioning
confidence: 99%
“…These clustered regions occupy only a limited surface area of the peritubular capillary wall (14,15). We have suggested that plasma proteins leak out through these limited regions of the peritubular capillary wall, distinct from the reabsorbing surfaces that comprise the major part of the capillary wall where the bulk of the tubular reabsorbate enters the capillary (16). We have further estimated that, under normal conditions, the reflexion coefficient of the reabsorbing surfaces is high (>0.99) and that virtually none of the extravasated protein caught up in the reabsorbtive stream will reenter the capillaries; almost all of the extravasated plasma proteins will drain from the interstitium through the lymph (11).…”
Section: Plasma Protein Circulation Through Kidney Cortical Interstitiummentioning
confidence: 99%